PERBANDINGAN FORMULA ENTERAL RENDAH LEMAK BERBASIS TEPUNG EDAMAME DENGAN FORMULA KOMERSIAL RENDAH LEMAK[Comparison of Edamame Flour Based Low Fat Enteral Formula with Commercial Low Fat Formula] - Siti Aliyah; Suci Indah Setiawati (Media Gizi Indonesia, 2018)
Dyslipidemia leads to atherosclerosis which is a risk factor for cardiovascular diseases. Edamame contains omega-3 fatty acids and phytochemical components such as isoflavones, sterols and saponins, and also high in fiber content. Edamame has been proved to have ability to decrease LDL cholesterol level. This research aims to analyze the comparison of edamame flour based low fat enteral formula with commercial low fat formula. This was a descriptive comparatif research design. Data collection was done by doing calculations on nutrient content and bioavailability protein, also organoleptic quality of low fat enteral formula with edamame flour substitution. The result showed that fat content of modified formula was 26.4% of total energy requirement and the value had met dietary requirement for dyslipidemia diet which is not more than <30% of total energy requirement. Type of fat in this formula largely contans unsaturated fats derived from omega-3 fatty acids of soy edamame and omega-9 fatty acids from olive oil. The value of  protein bioavailability which was shown from Amino Acid Score was 32.18, Theoretical Digestibility was 89.27, Net Protein Utilization was 28.73, Protein Worth of Eggs was 16.77, and Protein Eficiency Ratio was 4.51. The result of hedonic quality test showed that the color of low fat enteral formula with edamame flour substitution was light brown, the taste was sweet, the smell was typical edamame aroma, and had liquid consistency. Based on the comparison of commercial enteral formula with non-commercial enteral formula based on edamame flour, it can be concluded that edamame based flour enteral formula can be recommended as a non-commercial enteral formula for patients with dyslipidemia replacing commercial formula.